Impact of fiscal and monetary policy on nominal GDP - INAM, Zeeshan (KDI School, 2015)
The sluggish growth and rising unemployment is an alarming situation for policy makers to come up with some crucial policy measures to get rid of the problem. The present study was conducted to investigate the relative effect of both fiscal and monetary policy on nominal GDP. The famous St. Louis equation was used with Newey and West test to examine the policy response for the period of 1972-2013. The empirical evidences suggested that the relative effect of fiscal policy as compared to monetary policy is higher. Further, the study also used an interaction term with dummy variable to estimate the relative impact of both policies in recession. Our findings confirmed that fiscal policy has larger relative effect over monetary policy whether there is recession or not. We assumed that the dictatorship regime is the key determinant for higher relative effect of fiscal policy over monetary policy on nominal GDP. Therefore, on the basis of our findings, we may not only recommend to use fiscal instrument as a policy tool to surmount the recession and generate job opportunities for people adding into labor force annually but also the country needs to conduct independent monetary policy
Thesis(Master) --KDI School:Master of Development Policy,2015